Revolutionizing Language Learning: the Use of Digital Technologies, Call and AI Learning Apps in the EFL Context - Naumoska, Aneta; Naumoska Sarakinska, Biljana (South East European University, Tetovo, 2025)
The 21st century is marked by rapid technological advances, which have had an impact on all spheres of life, including education. As it is now impossible to imagine life without all the technological devices we have at our disposal, it is impossible to imagine the modern classroom without them, as well. Certainly, not incorporating all technology has to offer would be somewhat counter-productive, as the advantages are evident in terms of increasing learner motivation, making classes more fun, allowing for faster communication between teachers and learners, among others. However, teachers need to strike a careful balance between innovation and preservation as they reevaluate conventional language teaching paradigms in light of incorporating different CALL frameworks and digital technologies in the classroom, as well as numerous AI learning apps as efficient tools in enhancing EFL acquisition. This paper addresses these issues, the various aspects that may have an adverse effect not just in the sphere of education but in life, and compares two AI apps - Duolingo and TalkPal - in EFL learning.
Keywords: computer-assisted language learning (CALL), digital technologies, communication, language learning environment, technological dependence